The Role of Bhabinkamtibmas in Implementing Counseling to Prevent the Crime of Theft in the Jurisdiction of the Lembang Police - Virajati, Charlie Yudha (Police Studies Review, 2024)
The focus of this thesis research is motivated by theft which is very common. The most common criminal theft is motor vehicle theft. Some of the factors that cause the occurrence of fraud include the increase in the number of unemployed and children who drop out of school, the limited members of community protection (Linmas), the lack of active social organization and the increasing number of motor vehicles themselves. In the case of handling cases as stated, preemptive efforts made by the National Police in the form of counseling to all levels of society, especially motorcycle vehicle users, are very necessary to do, that is by developing community participation in efforts to prevent opportunities and opportunities for perpetrators of crimes to carry out theft theft. and theft of violence with two-wheeled motorized objects. This is where the role and function of Binmas is demanded to make pre-emptive efforts. One of them is in the form of counseling by Bhabinkamtibmas as the leading executor of the binmas function to carry out its main tasks in the frontier unit. Theories and concepts used to analyze and answer the problem of the Role of Bhabinkamtibmas in conducting counseling are the Role theory and management theory. The research method carried out by the author is field research using a qualitative approach, and data collection techniques by the author are by interviewing, observing, and studying documents. Based on the results of the study found the fact that in the implementation of counseling to the community still faces obstacles. Implementation of counseling in realizing Harkamtibmas there are several inhibiting factors Factors that become obstacles in the implementation of counseling are factors man, money, material, market. The author gives advice to the Cimahi Police Precinct precisely Lembang Police to conduct counseling by playing an active role and also overcoming external and internal factors. Likewise with the stake holders Able to evaluate and analyze the implementation according to the Perkap and SOP.